Nurturing Tomorrow’s Jurists: Rethinking the Indonesian Constitutional Court's Clerkship System through a Comparative Lens - Albar, Rafsi Azzam Hibatullah; Siregar, Eugenia Felicia Natiur; Al Asyari, Haekal (Universitas Negeri Semarang, 2023)
This paper dives into the clerkship system at the Indonesian Constitutional Court (MK), an independent judicial organ that holds high importance as the guardian of the constitution. While the court’s nine justices benefit from the existence of a clerk’s office, its work is still very limited to administrative matters. The paper begins by questioning whether the current system is sufficient to assist justices in their work and fulfill the larger aims of judicial clerkship. Its ultimate objective as a follow-up to the question is to identify ways to improve MK’s clerkship system. In order to assess the Indonesian clerkship system, a comparative analysis study of three other countries’ courts that similarly act as guardians of their respective constitutions – namely the Supreme Court of the United States, Constitutional Court of South Africa, and Supreme Court of India – is conducted. It is found firstly that there is indeed a need to change the clerkship system in MK as there are multiple ways in which clerks can help the court and benefit from it. Consequently, the changes that should be made run deep into the very purposes and roles of clerks, the structure of the committee or program, and the expected qualifications and selection process. By drawing inspiration from the three aforementioned courts, a contextualized adoption can be identified by taking into account Indonesia’s own circumstances.